Search-Based Software Engineering 7th International Symposium, SSBSE 2015, Bergamo, Italy, September 5-7, 2015, Proceedings - Barros, Márcio; Labiche, Yvan (Programming and Software Engineering, 2015)
This book constitutes the refereed proceedings of the 7th International Symposium on Search-Based Software Engineering, SSBSE 2015, held in Bergamo, Italy, in September 2015. The 12 revised full papers presented together with 2 invited talks, 4 short papers, 2 papers of the graduate track, and 13 challenge track papers were carefully reviewed and selected from 51 submissions. Search Based Software Engineering (SBSE) studies the application of meta-heuristic optimization techniques to various software engineering problems, ranging from requirements engineering to software testing and maintenance.